2019–2020 Florida Citrus Production Guide: Nematodes - Larry W. Duncan; Joe W. Noling; Renato N. Inserra (EDIS)
Integrated pest management (IPM) for nematodes requires (1) determining whether pathogenic nematodes are present within the grove; (2) determining whether population densities of some nematodes are high enough to cause economic loss; and (3) selecting a profitable management option. Attempting to manage nematodes may be unprofitable unless the above procedures are carefully followed. Similarly, some management methods pose risks to people and the environment, and therefore it is important to know that their use is justified by the actual conditions in a grove. This 3-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Larry W. Duncan, Joe W. Noling, and Renato N. Inserra, and published by the Entomology and Nematology Department, March 2019.